Efficacy and safety of reducing duration of infliximab infusion. Issue 2 (March 2014) - Fukuyo, Shunsuke; Saito, Kazuyoshi; Yamaoka, Kunihiro; Sawamukai, Norifumi; Hirata, Shintaro; Nawata, Masao; Iwata, Shigeru; Tanaka, Yoshiya
Abstract Objective. To evaluate the safety and efficacy of reducing the duration of infliximab infusion for rheumatoid arthritis (RA) treatment. Methods. The first 6 infliximab infusions were each administered over a 2-h period. If no adverse reaction was observed, infusion times were shortened to 1 h starting with the seventh infusion with further shortening to 30 min starting with the thirteenth infusion. Subjects were divided into two groups: shortened infusion time group, in which infusion times were shortened as above; and constant infusion time group, in which infusion time was 2 h. Incidence of infusion reactions and improvement in disease activity score for 28 joints (DAS-28) erythrocyte sedimentation rate (ESR) for total infusions were compared for the seventh to twelfth and thirteenth to eighteenth infusions. Results. The incidences of infusion reactions after the seventh to twelfth and thirteenth to eighteenth infusions in the shortened infusion time group were 0.53% and 0.58%, respectively. In the constant infusion time group, these were 0.70% and 0.67%, respectively. Furthermore, shortening the infusion duration did not affect the DAS-28 (ESR) improvement rate. Conclusions. We established that this stage-wise shortening of infusion duration, first to 1 h and then to 30 min, did not compromise the safety or efficacy of treatment.